Perancangan Busana Pesta Anak Perempuan Usia 8 – 10 Tahun Menggunakan Teknik Canadian Smock - Abdullah Rosidin; Sarah Rum Handayani (Institut Seni Indonesia Surakarta, 2022)
The design background of this work is to create design innovations by applying the canadian smock technique which is applied to girls' party clothes. This design is also intended to make the millennial generation re-recognize smock as a part of the craft art which is now rarely encountered, especially in Indonesia. In addition, this design will produce a product that is different from other party clothing products, by prioritizing aesthetic elements in children's party clothing.